Effectiveness of tenofovir and entecavir in nucleos(t)ide analogue-naive chronic hepatitis B: A protocol for systematic review and meta-analysis - Chen, Mao-bing (Medicine (Baltimore), 2019)
BACKGROUND: Chronic hepatitis b (CHB) is a serious problem worldwide. Tenofovir disoproxil fumarate (TDF) and entecavir (ETV) both are first-line drugs for CHB, but there is debate about which is more appropriate in nucleos(t)ide analogue-naive CHB. OBJECTIVE: To systematically evaluate the effectiveness and safety of tenofovir and ETV in nucleos(t)ide analogue-naive CHB. METHODS: The Web of Science, PubMed, The Cochrane Library, EMBASE, Clinical Trials, and China National Knowledge Infrastructure databases will be electronically searched to collect randomized controlled trials regarding the comparison between tenofovir and ETV in nucleos(t)ide analogue-naive CHB since the date of database inception to July 2019. Two researchers independently screened and evaluated the obtained studies and extracted the outcome indexes. RevMan 5.3 software will be used for the meta-analysis. RESULT: We will provide practical and targeted results assessing the effectiveness and safety of TDF and ETV for nucleos(t)ide analogue-naive CHB patients, try to compare the advantages of TDF and ETV. CONCLUSION: The stronger evidence about the effectiveness and safety of TDF and ETV for nucleos(t)ide analogue-naive CHB patients will be provided for clinicians. PROTOCOL REGISTRATION NUMBER: PROSPERO CRD42019134194.